(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
The rapid proliferation of Pentecostal churches in Abuja, Nigeria, has often been attributed to urbanisation. The names given to these churches are striking and far from arbitrary; rather, they are deliberate and creative coinages. Church founders employ a wide range of metaphors in naming their churches. These metaphors function not merely as labels but as communicative strategies through which identity is constructed, spiritual emphasis is indexed, and potential congregants are attracted. Although existing scholarship on church names has largely focused on classification, patterns, structure, and stylistic features, comparatively little attention has been paid to the metaphors underlying Pentecostal church naming practices. This paper therefore examines the metaphors embedded in Pentecostal church naming conventions. Drawing on Lakoff and Johnson’s (1980) Conceptual Metaphor Theory and Levinson’s (1983) theory of indexicality in pragmatics, the study analyses forty Pentecostal church names in Abuja, Nigeria. These names were obtained online from a directory of Pentecostal churches in Abuja. The findings reveal several recurring metaphorical themes, including metaphors of God, Christians, warfare, power, the church, nature, and transformation. These metaphors encapsulate doctrinal foundations, mission, and vision, while also serving as indicators of spiritual emphasis, ideology, and religious identity. In addition, they function as branding strategies for places of worship and as tools for persuasion, group cohesion, and socio-religious positioning. The study demonstrates that Pentecostal naming practices constitute a form of religious pragmatics in which metaphor operates as a powerful resource for encoding theology, shaping communal identity, and transforming physical spaces into linguistically “sacred” symbols.